Social media and social capital in online learning - Venter, A. (South African Journal of Higher Education, 2019)
Online learning affords student with an opportunity to collaborate with peers in furthering their learning. Open distance learning (ODL) institutions typically accommodate students from diverse educational backgrounds with disparate levels of access to technological resources. The mere existence of an online learning platform does not necessarily equate to student access to the collaborative learning opportunities. Online students need to be able to activate and customise those opportunities and establish social learning networks to further their studies. A qualitative study investigated how diverse students in an online learning module collaborated with peers in pursuit of their learning project at a large ODL university. It emerges that students engage in various formal and informal collaborative learning activities which constitute a personal learning environment (PLE). Social capital theory shows how different types of social ties in PLEs provide for bonding and bridging social capital; the combination of which serves the learning project by providing for both strong ties in supportive relationships between students and weak ties with knowledge generation capabilities between previously unacquainted students. The results can benefit designers and facilitators of online learning who want to capitalise on the inherent collaborative nature of online learning.